Assessing the effect of ultra-small phospholipid nanoparticles on biochemical parameters of carbohydrate and fat metabolism in patients with combined hyperlipidemia. (14th October 2021) - Zubareva, M; Kudinov, V; Artyushev, R; Rozhkova, T; Malyshev, P; Gornyakova, N; Baskaev, K; Sharf, T; Sergienko, I
Abstract: Background and aims: Based on the developed technology of preparation of ultra-small size phospholipid (PL) nanoparticles without the use of detergents/surfactants and stabilizers drug preparation, exhibiting hypolipidemic properties has been obtained. Preclinical and clinical studies have shown that phospholipid nanoparticles of 20–30 nm (PLN) have activated reverse cholesterol transport and reduced non-high-density lipoprotein cholesterol levels. The aim of the study was to compare the effect of PLN relative to placebo on the selected parameters of carbohydrate and fat metabolism in patients with combined hyperlipidemia. Methods: This Phase III, randomized, double-blind, placebo-controlled, parallel-group study was conducted at 4 centers. The patients (pts) received PLN or placebo (1:1), powder for oral solution preparation (500 mg PL/dose) orally 2 times per day for 12 weeks. Biochemical parameters of carbohydrate and fat metabolism were measured. The data is presented in M (s). Statistical analysis was performed using the Mann-Whitney U-test and the Wilcoxon sign rank test. P-value <0.05 was considered statistically significant. Results: A total of 100 pts with combined hyperlipidemia were randomized (age 35–70 years, males 58%). The mean age of patients was 56.4 (10.2) years, body-mass index (BMI) – 30.4 kg/m (2). Mean glucose, triglyceride (TG), fasting insulin (INS) and adiponectin (ADN) serum levels at baseline were 5.58 (0.9) mmol/l, 2.38 (0.6) mmol/l, 13.71 (6.03) mU/ml and 7.07 (2.25) μg/ml, respectively. At Week 12, PLN significantly reduced TG and insulin (p=0.03 and p=0.02, respectively). At the same time, the mean adiponectin level was increased (ns). The drug was well tolerated, and no clinically significant laboratory abnormalities were detected. Conclusions: PLN therapy is well tolerated with a favorable effect on the chosen parameters of carbohydrate and fat metabolism in patients with moderate combined hyperlipidemia. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Ministry of industry and trade, Ministry of Healthcare of the Russian Federation